SOSIALISASI BAHAYA MEROKOK DAN PENCEGAHAN PENYAKIT AKIBAT ROKOK BAGI KESEHATAN PADA SISWA SMP NEGERI 29 SEMARANG - Mukaromah, A H; Nuroini, F; Permatasari, A L; Maulydina, A P; Shofie, E A; Maldiny, FD; Vineila W, G; Kusumawati, M; Ariskasari , N; Setyasih, M V; Yinnisa, S; Istiyani, V (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2025)
This Community Service aims to socialize the Dangers of Smoking and Prevention of Diseases Caused by Smoking for Health to Students of SMP Negeri 29 Semarang. Cigarettes. The methods used are lectures, and posters. The activity was carried out on October 7-10, 2024, to 260 students of class IX of SMP N 29 Semarang. The results of this PKM before the socialization, students' knowledge about cigarettes is dangerous has a value of more than 5 as much as 80.7%. 50% of students know the definition of addictive substances and 50% of students know the definition of addictive substances, but the types of addictive substances contained in cigarettes, most students do not know. The negative impact of cigarettes on health for both active and passive smokers, students already understand. After the socialization, students of SMP N 29 Semarang already understand and know the content of cigarettes and addictive substances in cigarettes. 100% of students already know the content and addictive substances in cigarettes, and 92.3% of students are uncomfortable when someone smokes around them. In conclusion, students' knowledge of the dangers of smoking and prevention of diseases caused by cigarettes for health after socialization has increased